Predictive factors of uterine movement during definitive radiotherapy for cervical cancer. (15th October 2016) - Maemoto, Hitoshi; Toita, Takafumi; Ariga, Takuro; Heianna, Joichi; Yamashiro, Tsuneo; Murayama, Sadayuki
Abstract: To determine the predictive factors affecting uterine movement during radiotherapy (RT), we quantified interfraction uterine movement using computed tomography (CT) and cone-beam CT (CBCT). A total of 38 patients who underwent definitive RT for cervical cancer were retrospectively analyzed. We compared pre-RT planning CT ( n = 38) and intratreatment CBCT ( n = 315), measuring cervical and corporal movement in each direction. Correlations between uterine movement and volume changes of the bladder and rectum on all CBCT scans were analyzed using Spearman rank correlation analysis. Relationships between the mean uterine movement and patient factors were analyzed using the Mann–Whitney test. The mean corpus movement was: superior margin (cranio–caudal direction), 7.6 ± 5.9 mm; anterior margin (anteroposterior direction), 8.3 ± 6.3 mm; left margin (lateral direction), 3.3 ± 2.9 mm; and right margin (lateral direction), 3.0 ± 2.3 mm. Generally, the mean values for cervical movement were smaller than those for the corpus. There was a significant, weak correlation between changes in bladder volume and the movement of the superior margin of the corpus (ρ = 0.364, P < 0.001). There was a significant difference in movement of the superior margin of the corpus between the subgroups with and without a history of previous pelvic surgery ( P = 0.007). In conclusion, change in bladder volume and a history of previous surgery were significantly related to intrafractional corpus movement; however, our observations suggest that the accurate prediction of uterine movement remains challenging.